A high-strength, environmentally stable, self-healable, and recyclable starch/PVA organohydrogel for strain sensor. (5th December 2022) - He, Li; Ye, Dezhan; Weng, Sen; Jiang, Xiancai
Graphical abstract: Highlights: The ion-conductive SPETC organohydrogel was prepared by introducing ethylene glycol, TA and CaCl2 into starch/PVA composite hydrogel. The SPETC organohydrogels exhibited high mechanical properties, excellent environmental stability and frost resistance. The SPETC organohydrogel showed high recyclability due to the fully physically crosslinked network. The SPETC organohydrogel could be used to assemble the strain sensor ( GF = 2.96). Abstract: Conductive hydrogels have attracted great interest in the fabrication of flexible strain sensors. However, hydrogel-based strain sensors still have unresolved challenges, such as low mechanical strength, lack of frost resistance, easy dehydration, and non-recyclability, which have largely hindered their application. Herein, the ion-conductive starch/PVA/EG/TA/CaCl2 (SPETC) composite organohydrogel was prepared by the cyclic freezing-thawing method using starch and PVA as the gel backbone, water and ethylene glycol (EG) as the binary solvent, and Ca 2+ and Cl - as the conducting ions carriers. The SPETC organohydrogel exhibited high mechanical properties and showed excellent environmental stability and frost resistance. SPETC organohydrogel was fully physically cross-linked by non-covalent interactions such as hydrogen bonding and ligand bonding, and these reversible interactions can give the gel good recyclability. Moreover, benefiting from the superior mechanical response, SPETC organohydrogel can be assembled as a flexible wearable strain sensor for real-life motion monitoring.